(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The study location only resides in Vietnam with a focused group of all 28 commercial banks in Vietnam. The main source of statistics for this testing will come and be collected directly from the financial statement of all financial institutions for 2010 and 2017. In term of panel data analysis, this should require for the Hausman test in term of differentiation between fixed effects model and random effects model (Sheytanova, 2015). This should ensure the accuracy of the test result in term of the hypothesis testing’s power and size as well as in term of obtaining the consistent result. The result will be conducted in term of for each dependent variables and one for collaboration of all dependent variables. For the purpose of the T-test results, we will have to look at the t-statistic, t-distribution and degrees of freedom to determine a p-value (probability) which can also be utilized to determine whether the population means differ. The result expects to have the size of the bank indicating no influence but all other dependent variables shall have impacts on the profitability of the bank in term of financial performance. For the purpose of this thesis, the ultimate problem to be addressed and examined in term of the development of financial institutions in Vietnam for the fiscal year of 2010 and 2017. The element of financial data will be able to add and accompany the ultimate purpose of this thesis. The determination and factors contributing to the profitability of all commercial bank in Vietnam for the course of the year from 2010 to 2017 will be assessed and review in this thesis. After the analysing main determinants of banks’ profitability in Vietnam’s 28 commercial banks that we can conclude that the empirical findings are consistent with the expected results from the T-test above. The result expects to have the internal and external factors of credit and liquidity risk, management efficiency, the market concentration as well as competition and the local economic growth of all commercial banks reflecting in their and return of asset for profitability ratio. As a policy recommendation for management and authorities of the banks, I propose an enhancement in term of supervision for credit and liquidity risk of banks (especially in term of implementation of Basel II) and the inspiring of banking competition and introduction of the products. For banks’ management level of decision making, I also indorse to monitor the credit and liquidity risk indicators, to expand the sources of revenues and to improve costs from operations perspectives. The limitation will be on the secondary source of data as well as the selection of determinants being on the previous studies and works of literature but no in the Vietnam market. As a future direction of research, I intend to deepen the analysis by extending the period as well as expanding the comparison to other developing countries in the region.